Automated mining of packet signatures for traffic identification at application layer with apriori algorithm - LIU Xing-bin1; YANG Jian-hua1; XIE Gao-gang1; HU Yue1 (Tongxin xuebao)
Automatic and accurate extraction packet signatures are the foundation of the precise traffic identification at application level. A method which can automatically extract the packet signatures of characteristic string and packet length for traffic identification at application layer was proposed. The identification rate, accuracy rate, positive identifi-cation error rate and negative identification error rate have been verified with experiment on some traces to valid the mined signatures.